Tanggapan Teologis Andreas A. Yewangoe Terhadap Otonomi Daerah di Indonesia Pada Era Reformasi - Arthur Aritonang (Program Pascasarjana UKIM, 2020)
This article examines deviations from the original purpose of the regional autonomy system in the Reformation era. Since the beginning, the local autonomy system was a response to a centralized government system during the New Order regime. The implementation of regional autonomy so that each region can regulate, develop, and advance its region. However, the spirit of regional autonomy has been distorted due to public policies' existence through a set of rules that impose religious law, which ultimately limits the development of other religions. In reality, regional / regency regulations with religious nuances clash with the Republic of Indonesia's existing constitution. This study uses the literature method approach, which focuses on the topic of regional autonomy as well as conducting interviews with national figures Andreas A. Yewangoe because his thoughts will be raised in responding to deviations from the original purpose of the formation of regional autonomy policies in Indonesia. In conclusion, Yewangoe gave a theological response so that matters of religious law were aimed at his religious group, not being forced to be applied in a heterogeneous public space to create democracy in Indonesia following the principles of humanity and justice for Indonesian people.